2009
DOI: 10.1002/hed.21013
|View full text |Cite
|
Sign up to set email alerts
|

Marginal mandibular nerve injury during neck dissection and its impact on patient perception of appearance

Abstract: Background. Neck dissection to remove cervical lymph nodes is common practice in head and neck cancer management. The marginal mandibular nerve may be injured during neck dissection, particularly of level 1. The rate of injury to this nerve is underreported in the literature and its impact on patients is not well defined.Methods. An observational study was undertaken on patients who had undergone neck dissection over a 5-year period. The patients were examined for weakness and given a questionnaire related the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 14 publications
0
42
1
Order By: Relevance
“…Multiple studies have now demonstrated that the facial nerve can be weak post-operatively despite anatomical and neurophysiological confirmation of its integrity due to factors including traction, devascularisation or the conduction block due to diathermy current during flap elevation [15,16]. The gross anatomical preservation of the nerve can still result in weakness as seen by a report which demonstrates that up to 23% of patients have a lower number of functional motor units in the orbicularis oris despite clear preservation [17].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have now demonstrated that the facial nerve can be weak post-operatively despite anatomical and neurophysiological confirmation of its integrity due to factors including traction, devascularisation or the conduction block due to diathermy current during flap elevation [15,16]. The gross anatomical preservation of the nerve can still result in weakness as seen by a report which demonstrates that up to 23% of patients have a lower number of functional motor units in the orbicularis oris despite clear preservation [17].…”
Section: Discussionmentioning
confidence: 99%
“…1 The most common causes of paralysis of the MMN are iatrogenic injuries of the nerve during operations in the submandibular or parotid regions. 2 …”
mentioning
confidence: 99%
“…Much attention has been drawn to the frequency of injury of the spinal accessory nerve after neck dissection [15,19,22], whereas few studies have reported on the actual frequency of permanent injury of the MMN in conjunction with neck dissection [3,15,16,22]. Paralysis of the MMN was noted in 18-21% of the patients in whom it was intended to preserve the nerve during the operation [3,15,16,22]. In our study, the overall risk of MMN paresis was 16.8% (19/113; table 1) at the clinical control 2 weeks postoperatively as regards dissection in level I to V. We found a statistically signiWcantly higher frequency of MMN injury after the combination of parotic cancer surgery and neck dissection (33.3%) as compared with the corresponding frequency after oral cancer surgery and neck dissection (13.7%).…”
Section: Discussionmentioning
confidence: 99%
“…1). However, the risk of injury to the MMN during neck dissections for malignancies has only scarcely been addressed in the medical literature [15,16]. Dissection for removal of possibly metastatic lymph nodes in level I B resulted in injury of the MMN in 18-21% of the cases even though preservation of the nerve function was intended during the operations [3,16].…”
Section: Introductionmentioning
confidence: 98%